Exponents
Solve this-
Attachments:
![](https://hi-static.z-dn.net/files/df3/f5afa4b0d4533396cdf4c5beafc3752b.jpg)
Answers
Answered by
0
hope this will help you
Attachments:
![](https://hi-static.z-dn.net/files/df5/a57f9afd7eb8c519b8d334caf45d157e.jpg)
Answered by
3
(-1/2)^-4 × (5/6)^-4
= {(-1/2)×(5/6)}^-4
[ a^m × b^n = (ab)^n]
= (-5/12)^-4
= (-12/5)^4
[ 1/a^-m = a^m]
= (12/5)^4
___________________________________
(3/4)^1 × (4/15)^-1
= 4/3 × 15/4
[ (a/b) ^-m = (b/a)^m]
= 15/3
= 5
________________________________
= {(-1/2)×(5/6)}^-4
[ a^m × b^n = (ab)^n]
= (-5/12)^-4
= (-12/5)^4
[ 1/a^-m = a^m]
= (12/5)^4
___________________________________
(3/4)^1 × (4/15)^-1
= 4/3 × 15/4
[ (a/b) ^-m = (b/a)^m]
= 15/3
= 5
________________________________
Similar questions